Participatory action planning in the peri-urban interface: the twin city experience, Hubli-Dharwad, India - Halkatti, Meera; Brook, Robert; Purushothaman, Sangeetha (2003)
This paper describes the process of participatory planning in five peri-urban villages in the Hubli-Dharwad twin city region. The objectives of the participatory planning project included enhancing the livelihoods of the poor and managing the natural resource base. The paper describes the characteristics of the villages involved and their specific peri-urban aspects; the tools used and the participatory planning process; the main issues which emerged from the process and their relevance to different groups (women, landowners, landless and lower castes). It also summarizes the main lessons learnt: what worked, the major problems and how these were addressed. - Reproduced.
Keywords: Participatory development